Time course analysis of mechanical ventilation‐induced diaphragm contractile muscle dysfunction in the rat. (31st July 2014) - Corpeno, R.; Dworkin, B.; Cacciani, N.; Salah, H.; Bergman, H.‐M.; Ravara, B.; Vitadello, M.; Gorza, L.; Gustafson, A.‐M.; Hedström, Y.; Petersson, J.; Feng, H.‐Z.; et al.
<x xml:space="preserve">Abstract</x> Key points Weaning from mechanical ventilation (MV) of long‐term intensive care unit (ICU) patients is delayed by impaired respiratory muscle function; however, the mechanisms that cause the impairment are not fully understood. A novel experimental rat ICU model was used for time‐resolved analyses (6 h to 2 weeks) of the effects of MV on diaphragm muscle fibre structure and function, and on gene and protein expression. A prompt and progressive decline of diaphragm muscle fibre function, preceding atrophy, occurred with MV, and at the end of 2 weeks residual diaphragm muscle fibre function was <15% of control levels. Cellular and subcellular analyses indicated that oxidative stress‐triggered protein modifications had significantly diminished diaphragm muscle fibre function. The novel finding that activation of proteolytic pathways and regulation of contractile protein synthesis were different in diaphragm and limb muscles has direct implications for the design of muscle‐specific intervention strategies. Abstract Controlled mechanical ventilation (CMV) plays a key role in triggering the impaired diaphragm muscle function and the concomitant delayed weaning from the respirator in critically ill intensive care unit (ICU) patients. To date, experimental and clinical studies have primarily focused on early effects on the diaphragm by CMV, or at specific time points. To improve our understanding of the mechanisms underlying the impaired diaphragm muscle function in response to mechanical ventilation, we have performed time‐resolved analyses between 6 h and 14 days using an experimental rat ICU model allowing detailed studies of the diaphragm in response to long‐term CMV. A rapid and early decline in maximum muscle fibre force and preceding muscle fibre atrophy was observed in the diaphragm in response to CMV, resulting in an 85% reduction in residual diaphragm fibre function after 9–14 days of CMV. A modest loss of contractile proteins was observed and linked to an early activation of the ubiquitin proteasome pathway, myosin:actin ratios were not affected and the transcriptional regulation of myosin isoforms did not show any dramatic changes during the observation period. Furthermore, small angle X‐ray diffraction analyses demonstrate that myosin can bind to actin in an ATP‐dependent manner even after 9–14 days of exposure to CMV. Thus, quantitative changes in muscle fibre size and contractile proteins are not the dominating factors underlying the dramatic decline in diaphragm muscle function in response to CMV, in contrast to earlier observations in limb muscles. The observed early loss of subsarcolemmal neuronal nitric oxide synthase activity, onset of oxidative stress, intracellular lipid accumulation and post‐translational protein modifications strongly argue for significant qualitative changes in contractile proteins causing the severely impaired residual function in diaphragm fibres after long‐term mechanical ventilation. For the first time, the present study demonstrates novel changes in the diaphragm structure/function and underlying mechanisms at the gene, protein and cellular levels in response to CMV at a high temporal resolution ranging from 6 h to 14 days.